The Effects of Link N and Bone Marrow-Derived Mesenchymal Stem Cells on the Regeneration of Intervertebral Disc. (May 2014) - Mwale, F.; Wang, H. T.; Roughley, P. J.; Antoniou, J.; Haglund, L.
Introduction: Link N is a naturally occurring peptide that can stimulate regeneration of the intervertebral disc (IVD). IVD repair can also potentially be enhanced by mesenchymal stem cell (MSC) supplementation to maximize extracellular matrix production. In a previous study, we have shown that Link N can inhibit osteogenesis and increase the chondrogenesis of MSCs in vitro. The aim of the present study is to determine the effects of injecting MSCs and Link N alone or together on the repair of degenerated discs. Materials and Methods: The largest first four caudal discs with intact cartilaginous endplates were isolated from the tails of 24- to 30-month-old bovines. After a 3-day preconditioning period, the discs were injected with 100 μg trypsin in 75 μL PBS, to induce degeneration. They were then cultured for another 4 days, followed by the injection of MSCs (10 5 ), Link N (75 μg), or a combination of MSCs and Link N, in a final volume of 75 μL PBS. Seven of the trypsin-treated discs were injected with PBS alone to serve as a degeneration control. After the discs were cultured for another 14 days, the extracellular matrix (ECM) proteins and proteoglycans were extracted from the inner nucleus pulposus of the discs by guanidinium chloride. Sulfated glycosaminoglycans (GAGs) were analyzed in tissue extracts ( n = 7/group) by the dimethyl methylene blue (DMMB) dye-binding assay. The expression of type II collagen was analyzed by Western blot. To track the MSCs after injection, MSCs were labeled with PKH67 and observed under confocal microscopy when the discs were dissected. Results: After injection, MSCs were distributed throughout the discs and retained their morphology. When the trypsin-treated discs were injected with PBS only, the final GAG concentration in the ECM was 15.12 µg/mg wet weight tissue. When the degenerated discs were injected with MSCs only, the GAG concentration increased to 25.66 µg/mg wet weight tissue. When the degenerated discs were injected with Link N alone or both Link N and MSCs, the GAG concentrations increased to 29.63 and 32.66 µg/mg wet weight tissue, respectively. Compared with the degeneration control, the expression of type II collagen also increased when the degenerated discs were injected with MSCs and Link N, either alone or together. Conclusion: MSCs and Link N can both increase GAG production in degenerated discs, with Link N showing a greater effect than MSCs when administered separately. However, an additive effect was found when MSCs and Link N were administered together. The injection of MSCs and Link N can also increase the expression of type II collagen in the degenerated discs. Thus, the administration of MSCs and Link N has therapeutic potential in intervertebral disc repair. Disclosure of Interest None declared